Implementation of the RSPO International Standard: Evaluation of Substantive Success and Systemic Constraints for Oil Palm Smallholders - Azizah, Nur; Prakoso, Cathas Teguh; Saipul, Saipul (SIGn Journal of Social Science, 2025)
The demands of the green economy and RSPO standards have compelled a global transformation of palm oil governance. However, an empirical anomaly exists in Paser Regency, where the massive expanse of smallholder plantations contrasts sharply with the low rate of certification adoption among oil palm smallholders. This study aims to evaluate the level of substantive success and unravel the root of systemic constraints in the implementation of RSPO standards for oil palm smallholders using Merilee S. Grindle’s theoretical framework of policy implementation. Adopting a qualitative approach with a descriptive-analytical design, data were gathered through technical triangulation involving in-depth interviews, observations, and document studies, and subsequently analysed by dissecting the variables of policy content and implementation context. The evaluation results demonstrate that the policy instrument has successfully transformed the governance behavior of a minority group of oil palm smallholders through the rationality of premium price incentives. Nevertheless, these achievements have not been replicated on a mass scale due to the administrative pathology of the local government. Local governments have been degraded into passive administrators due to the double burden of national regulations and international standards. This state institutional failure is validated through the paralysis of land legality administrative services, the absence of audit financing subsidies, and the lack of a persistent technical assistance system. This study concludes that the failure of sustainability adoption is purely rooted in the structural weaknesses of public services rather than the cultural rejection of oil palm smallholders. This study recommends affirmative interventions, including bureaucratic simplification of land title processes, specific budget allocations, and the institutionalisation of field assistance, to prevent oil palm smallholders from being eliminated from the global supply chain.